Chicago Paper - Discussion of paper of Prof. Christy (See p. 444) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1894)
Prof. G. W. MAYNARD, New York City (communication to the Secretary): Prof. Christy, in his admirable paper on "The Growth of American Mining Schools," has overlooked the work done by the Rensselaer Polytechnic Institute in its department of mining and metallurgy. This oversight is naturally due to the fact that the department was, for lack of money, discontinued in 1871. It was organized by the writer in 1867, starting with ten students, who had already completed the first two years of the civil engineering course in the Institute. The course covered two years, specifically devoted to mining, metallurgy and assaying, which, in connection with the two years' drill in the civil engineering department made a four years' course. During the four years of the existence of the department, thirty-five students took the course, of whom twentyfive graduated; and of this number eight have been members of the Institute of Mining Engineers, and the majority of them have occupied high positions in the profession. The equipment of the department was, at that time, second only to that of the Columbia School of Mines. As Prof. Christy has cited other institutions which are not distinctively mining schools, but in which the ruining course was subordinate to other courses, it seems to me that the work in this line carried out by the oldest engineering school in the country may very properly be referred to. In addition to the regular mining course, a special course in assaying was given; and many young men were here prepared for positions in the mines and metallurgical works of the west. PROF. George F. Swain, Boston, Mass.: I have listened with great interest to Prof. Christy's valuable paper, but there is one conclusion at which he arrives that appears to me entirely unjustifiable, and to which I desire to take exception. Prof. Christy finds that of the total wage-earners in the United States in 1880,10.41 per cent. were employed in " trade and transport;" 20.24 per cent. in " manufactures and mechanics," and 1.83